Copper Decorated on Fluorine Doped Tin Oxide as a Transparent Conductor Oxide for Photovoltaic Energy by DSSCs (Global Journal of Science Frontier Research, 2021)
In this work, films of fluorine doped tin oxide (FTO) with and without copper have been successfully synthesized by spray pyrolysis on conductive transparent substrates without acid addition. Sprayed film samples were used in the determination of photovoltaic parameters in the dye-sensitized solar cells (DSSCs), including open-circuit voltage (Voc), short circuit current density (Jsc), fill factor (FF), efficiency (ƞ), shunt (Rshunt) and serial (Rserial) resistances. Characterization techniques determined the sheet electrical resistance, optical transmittance, thickness, band gap, topographical and structural characterizations, and flat-band potential of the sprayed films. The X-rays diffraction showed peak distribution of the sprayed products similar to the tin dioxide phase. There was morphological change, with smaller and more compact grains by adding copper. Also, conduction band edge, sheet resistance, optical transmittance and optical band gap change as function of the amount of copper.
Keywords: spray pyrolysis; characterization; photovoltaic; environmental